Cosmologia e estrutura de longo curso do catolicismo na dinâmica da modernidade (Cosmology and long term structure of catholicism in the dynamics of modernity) - DOI: 10.5752/P.2175-5841.2011v9n23p746 - Camurça, Marcelo Ayres (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2012)
A tendência de uma sociologia do catolicismo contemporâneo no país nestes últimos anos foi de reduzi-lo a uma instituição política e social movida por interesses de poder no campo religioso e no espaço público, dispensando a mediação de sua cosmologia como pano de fundo de sua atuação. A partir do livro pioneiro de Roberto Romano (1976) que resgata o papel da cosmologia católica na sua intervenção pública, e seguindo os estudos de Sanchis (1994) e Steil (1996) que chamam a atenção para o seu perfil de “estrutura de longa duração” que se (re)combina com os estilos das épocas que atravessa, a intenção deste texto é detectar numa hermenêutica de aspectos cruciais da Teologia católica e em dimensões estruturais de sua configuração, condutas e comportamentos pelo qual o catolicismo se faz presente na modernidade. Neste particular, a cosmologia não vai engendrar um comportamento holista-tradicional mas vai expressar-se traduzida para os códigos contemporâneos seja do individualismo, da subjetividade, da cultura psi, da auto-ajuda e da expresividade emocional e corporal. Palavras chave: Catolicismo. Cosmologia. Modernidade. Abstract: The trend in contemporary sociology of Catholicism in Brazil has been to reduce Catholicism to a political and social institution moved by the interests of power in religious as well as public spheres, ignoring the intervening role of its cosmology as a background for its actions and postures. The article takes as a starting point Roberto Romano’s (1976) pioneer work in the field, where the author reinstates the role of catholic cosmology in processes of institutional public intervention. It has equally drawn inspiration from Sanchis (1994) and Steil’s (1996) studies stressing on Catholicism’s institutional profile as a ‘structure of long duration’ that interacts with the various ways of living of different times and spaces. Accordingly, the main goal of the article is to identify in a hermeneutics of crucial aspects of Catholic theology and in structural dimensions of its configuration, the attitudes and behaviors that inform Catholicism’s presence in modernity. In this way, cosmology doesn’t underpins any traditional holistic behavior but finds expression in translations of contemporary codes like those of individualism, subjectivity, psy culture, self-help and emotional and bodily expressions. Key-words: Catholicism. Cosmology. Modernity.